Investigação dos efeitos das impurezas alcalinas e hidrogênio no quartzo submetido à eletrodifusão e radiação ionizante - Rosa, Rafael Augusto dos Anjos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In the present study, we investigated the effects of alkali ions Na+ , Li+ replaced by ion H+ and Na+ in the center related to the aluminum that is a found naturally in motrices natural quartz. Measurements of optical absorption in the visible and ultraviolet region and measures infrared samples of natural quartz that have passed or not by electrodiffusion process were performed. An effect of browning in citrine quartz was investigated when exposed to the sun , correlating with the centers studied in this work, [ AlO4/H]0 , [ Li-OH ] and [Na-OH] , identifiable in the infrared region in the centers [AlO4]0 and E’ that are identifiable in the optical absorption spectrum. The existence of such centers, centers called impurities is facilitated by the presence of a structural channel quartz, which allows the entry of ions such as substitutional Al3+ substitutional and interstitial as Na+, Li+ and H+ along the crystal quartz chain . The samples were submitted to gamma radiation dose of approximately 20kGy , the outcome was analyzed based on the centers and the effects of electrodiffusion were analyzed by spectroscopy, UV- Vis and IR region. Infrared analysis indicated that the hydrogen electrodiffusion in citrine and hyaline quartz was successful , since there is an increase in the center [AlO4/H]0 and a decrease in the [Li-OH] , located in the band at 3484cm -1. The interaction between gamma radiation and quartz causes the centers related to the presence of hydrogen with aluminum increase , because the radiation to excite the atoms of the quartz network ultimately directly affect the centers whose compesator load are the alkali atoms Li+ , Na+ and K+ center [AlO4/M]0 , then there is compensation for hydrogen atoms , thus forming more centers [AlO4/H]0 . The appearance of bands at 430 and 620 nm associated to the center [AlO4]0 in the citrine and hyaline quatz after irradiation, enables us to state that ...

No presente trabalho, investigaram-se os efeitos dos íons alcalinos Na+, Li+ substituídos pelo íon H+ e Na+ nos centros relacionados ao alumínio que é uma impureza encontrada naturalmente nas matrizes de quartzo natural. Foram realizadas medidas de absorção óptica na região do visível e do ultravioleta, assim como medidas no infravermelho de amostras de quartzo natural que passaram ou não pelo processo de eletrodifusão. Foi investigado um efeito de escurecimento no quartzo citrino quando este é exposto ao sol, correlacionando com os centros estudados no presente trabalho, [AlO4/H], [Li-OH] e [Na-OH], identificáveis na região do infravermelho e os centros [AlO4]0 e E’ identificáveis no espectro de absorção óptica. A existência desses centros, chamados de centros de impurezas, é facilitada pela presença de um canal estrutural no quartzo, o qual permite a entrada de íons substitucionais como Al3+ e intersticiais Na+, Li+ e H+ junto a cadeia cristalina do quartzo. As amostras foram submetidas à radiação gama de dose aproximada a 20kGy, o resultado foi analisado com base nos centros estudados e os efeitos da eletrodifusão foram analisados por espectroscopia na região do UV-Vis e Infravermelho. A análise infravermelha indicou que a eletrodifusão de hidrogênio no quartzo citrino e hialino foi bem sucedida, uma vez que observa-se um incremento no centro [AlO4/H]0 e um decréscimo no centro [Li-OH], localizado na banda em 3484cm-1. A interação entre a radiação gama e o quartzo faz com que os centros relacionados à presença de hidrogênio com o alumínio aumentem, pois, a radiação ao excitar os átomos da rede do quartzo acaba por afetar diretamente os centros cujo compensador de carga são os átomos alcalinos Li+,Na+ e K+ do centro [AlO4/M]0, havendo então a compensação por átomos de hidrogênio, formando então mais centros [AlO4/H]0. O aparecimento das bandas em 430 ...
Keywords: Quartzo; Eletrolise; Radiação ionizante; Fourier, Espectroscopia de infravermelho por transformada de; Espectroscopia de ultravioleta; Electrolysis